EFFECT OF UREA FERTILIZER AND WEED EXTRACTS SPRAY (JAMIX AND ALGERIAN ON VEGETATIVE,YIELD AND QUALITY OF PEAS (Pisum sativum L . - Waleed B.A. AL-Lelah (Mesopotamia Journal of Agriculture)
This experiment was carried out at the field of Horticulture and landscape Design Department , College of Agriculture and Forestry , University of Mosul , in a clay loam soil texture. during the growing season ( 2009/2010) to study the effect of five levels of fertilizer (Two levels of Nitrogen fertilizer and sea plant extracts of Jamix and Algerian). In the growth and yield of Peas(Little marvel). The following characters were studied: plant length(cm),number of branch / plant , dates of flowering and maturity/day , pod length(cm) , average pod weight (gm) , number of pods /plant , number of seeds/pod , 100seed weight (gm) , yield of green and dry pod weight, yield of dry seeds and biological yield(gm/plant).The results showed that there were significant differences between treatment means for all the studied characters , except for dates of flowering and maturity and pod weight (gm) , seed number/pod and 100 seed weight (gm).The results showed that the treatment of nitrogen fertilizer (kg/Donum) gave a high significant level compared with other treatments for the number of branch/plant , flowering date , and number seeds per pod, while the Algren treatment was the best for the characters plant height , pod maturity date and pod length. Aljamex treatment was superior for the characters number of pods/plant and 100 seed weight, total yield of green and dry pods and dry seed yield and biological yield.